Relaciones entre los estilos pictóricos, la tecnología de la cerámica y las áreas funcionales del CA42 del num de las huacas de Moche. - Ramos Mar, Adriana Victoria (2017)
Moche decorated ceramics possessed a high ideological value as a means by which the elite made known its power, identity and wealth. In this panorama there are three types of decoration of the Moche pottery, using the decorative base of red slip, cream or the natural color of the paste. The Moche society between 600 d. C. or 650 d. C, was experiencing a time of crisis and social reorganization, this time corresponds to the last two occupations of CA 42 in which two behaviors were defined, During the last occupation within the different areas of the set, no preferences are appreciated for some particular decorative style, whereas in the last occupation if they have preferences for some pictorial types in a particular sector, this last behavior would be showing us two options, first that they are two groups using this architectural set or that the same group is characterizing the function of the area with a different decoration.